The Influence of Project-Based Learning Models on Collaboration Skills and Science Learning Outcome for Junior High School - Luh Putu Welly Sarjani; I Wayan Suastra; I Wayan Subagia (Postgraduate, University of Mataram, 2023)
The aim of this research was to analyzed the differences in collaboration skills between students taught with a project-based learning model and conventional learning model in science subjects. The type of research includes quasi-experiments with a pretest-posttest non-equivalent control group design. The sampling technique used was nonprobability sampling. The population consisted of eleven classes in class VII, and the sample used was four classes. The research instruments were observation of collaboration skills and learning outcomes tests. The data obtained were collaboration skills scores and pretest and posttest scores on temperature and heat material. Data were analyzed using descriptive analysis techniques and inferential analysis (one-way MANOVA) with a significance level of 5%. Before testing the hypothesis, prerequisite tests are carried out (normality, homogeneity of variance, covariance, linearity, and correlation between variables). The results showed that significant differences in collaboration skills and science learning outcomes both simultaneously and separately between students taught using the project-based learning model and students taught using the conventional learning model with a p value <0.05. Referring to the results, it was concluded that there were differences in collaboration skills and learning outcomes between students who were taught using the project model, which was better than the conventional model